Zmiany sekularne w budowie i proporcjach ciała piłkarzy ręcznych = Secular changes in the body build and body proportions of the handball players - Anna Burdukiewicz; Jadwiga Pietraszewska; Aleksandra Stachoń; Justyna Andrzejewska; Marcin Basiak (Kazimierz Wielki University, 2016)
Burdukiewicz Anna, Pietraszewska Jadwiga, Aleksandra Stachoń, Andrzejewska Justyna, Basiak Marcin. Zmiany sekularne w budowie i proporcjach ciała piłkarzy ręcznych = Secular changes in the body build and body proportions of the handball players. Journal of Education, Health and Sport. 2016;6(9):367-378 eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.62003 http://ojs.ukw.edu.pl/index.php/johs/article/view/3840       The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.08.2016. Revised 25.08.2016. Accepted: 06.09.2016.     Zmiany sekularne w budowie i proporcjach ciała piłkarzy ręcznych   Secular changes in the body build and body proportions of the handball players     Burdukiewicz Anna1, Pietraszewska Jadwiga1, Aleksandra Stachoń1, Andrzejewska Justyna1, Basiak Marcin2   1 Zakład Antropologii Fizycznej, Akademia Wychowania Fizycznego we Wrocławiu 2 Akademia Wychowania Fizycznego we Wrocławiu, student   Adres do korespondencji: Anna Burdukiewicz Akademia Wychowania Fizycznego we Wrocławiu Zakład Antropologii Fizycznej Al. I.J. Paderewskiego 35, P-2 51-612 Wrocław Telefon: + 48 71 347 3313 E-mail: anna.burdukiewicz@awf.wroc.p   Słowa kluczowe: zmiany długofalowe, antropometria, piłkarze ręczni   Streszczenie: Cel. Celem pracy jest zbadanie przejawów trendu sekularnego w budowie i proporcjach ciała profesjonalnych graczy piłki ręcznej badanych w 1977 i 2014 roku. Materiał i metody. Ogółem zmierzono 51 mężczyzn. W opracowaniu wykorzystano wyniki pomiarów cech somatycznych: masa ciała, wysokość ciała, długość kończyny górnej, długość kończyny dolnej, wysokość siedzeniowa, zasięg kończyn górnych, obwody tułowia (obręczy barkowej, klatki piersiowej przez punkt xiphoidale, bioder), obwody segmentów kończyn (ramienia, przedramienia, uda, podudzia), fałdy skórno-tłuszczowe (pod dolnym kątem łopatki, na ramieniu, nad grzebieniem biodrowym, na podudziu). Cechy somatyczne posłużyły do wyliczenia wskaźników proporcji ciała oraz komponentów budowy (endomorfia, mezomorfia, ektomorfia). Wszystkie analizowane zmienne zostały poddane analizie statystycznej. Wyniki. Piłkarze ręczni z obu grup są wysokorośli, mają długie kończyny dolne i średnią długość korpusu ciała oraz masywną sylwetkę ciała. Odnotowano dodatni kierunek trendu w poziomie rozwoju wszystkich cech somatycznych za wyjątkiem zasięgu kończyn górnych. W analizowanych proporcjach ciała wystąpiła wyraźna tendencja do powiększenia relatywnej długości korpusu ciała, a ponadto sylwetka stała się bardziej androidalna. Wnioski. Kierunek zmian sekularnych w cechach wysokościowych i długościowych nie różni się od zaobserwowanego w populacji generalnej. Znaczne powiększenie masywności segmentów kończyn oraz komponentu mezomorfii należy wiązać ze zmianami w treningu sportowym.   Key words: long-term changes, anthropometry, handball players   Abstract: Aim. The aim of the paper is to investigate a secular trend in body build and proportions of professional handball players examined in the years 1977 and 2014. Material and methods. There were measured in total 51 males. In the analysis, the following measurements of the somatic features were used: body mass, body height, lower extremity length, sitting height, arm span, girths of trunk (shoulder, chest throught point xiphoidale, hip), the circumferences of the segments of extremities (arm, forearm, thigh, calf), skindfolds (subscapular, triceps, supraspinale and calf). The somatic features were used to calculate the body proportions' indexes as well as the components of body build (endomorphy, mesomorphy, ectomorphy). All the variables were analyzed with statistical methods. Results. The handball players from both groups are high, have long lower extremities, an average length of trunk and massive body posture. There were noticed positive direction of trend in a level of development of all somatic features except the arm span. Among the analyzed body proportions, a significant tendency to enlarging the relative length of body trunk was observed and the trunk became more android. Conclusions. The direction of secular changes in the features of body high and length do not differ from these observed in a general population. The significant enlargement of body segments' massiveness in extremities as well as mesomorphy component should be connected with the changes in sport training.